Bridges : engineering masterpieces - Zettwoch, Dan (2022)
"Follow Bea, Archie, Trudy, and Spencer (otherwise known as the BATS!) as they crisscross the globe using every type of bridge: beam, arch, truss, and suspension. From ancient low-slung rope bridges to modern hi-tech towers of steel, they'll traverse 'em all. Their journey will take them through history and connect them with new ideas and different cultures. Along the way they'll identify the dangerous forces trying to bring bridges crashing down, and how to defeat them--through engineering!"--Provided by publisher
"Get to know your universe!"--Cover
Chiefly illustrated.
Includes bibliographical references (page 120).
Ages 8-12
A Junior Library Guild selection.
Keywords: Bridges -- History -- Juvenile literature; Bridges -- History -- Comic books, strips, etc; Bridges -- Comic books, strips, etc; Civil engineering -- Comic books, strips, etc; Bridges -- Juvenile literature; Civil engineering -- Juvenile literature; Bridges -- History -- Cartoons and comics; Bridges -- Cartoons and comics; Civil engineering -- Cartoons and comics; Cartoons and comics; JUVENILE NONFICTION -- Comics & Graphic Novels -- Science & Nature; JUVENILE NONFICTION -- Science & Nature; JUVENILE NONFICTION -- Technology -- How Things Work-Are Made; Bridges; Civil engineering; Bridges -- History -- Comic books, strips, etc; Bridges -- Comic books, strips, etc; Civil engineering -- Comic books, strips, etc; Graphic novels; Nonfiction comics; Creative nonfiction; Comics (Graphic works); Graphic novels; Educational comics; Comics (Graphic works); Creative nonfiction; History; Juvenile works; Nonfiction comics; Nonfiction comics; Educational comics; Graphic novels; Creative nonfiction; Comics (Graphic works)